The effects of transcranial direct current stimulation on EEG power and complexity of ischemic stroke - Xi, Wang; Song, Guoqiang; Ma, Zhizhao; Liu, Liqiang (Frontiers in Neuroscience, 2025)
Transcranial direct current stimulation (tDCS), has shown therapeutic potential for ischemic stroke, but the neural oscillatory mechanisms of its therapeutic effects remain incompletely elucidated. Based on the rat model and clinical stroke patients, this paper combines multiple indicators such as electroencephalography (EEG) relative power (RP), Lempel-Ziv complexity and sample entropy to investigate the mechanism by which tDCS modulates neural oscillations in ischemic stroke. The results indicated that tDCS substantially reduced the RP of the δ frequency band, enhanced the normal oscillation of the α frequency band, and improved the complexity index of the EEG signals. These findings suggest that tDCS could facilitate the recovery following ischemic stroke through the modulation of EEG rhythms.